The mediating effect of technological orientation on the relationship between project management process and infrastructure performance of road and transport authority in UAE - Ali, Abdalla Ahmed Hassan Ahmed Al (Tanjong Malim, 2024)
The mediating effect of technological orientation on the relationship between project management process and infrastructure performance of road and transport authority in UAE by Ali, Abdalla Ahmed Hassan Ahmed Al